Education placement of children with autism in Lesotho: Challenges and opportunities - Mahlape Tseeke; Dineo Paulina Tseeke (Perspectives in Education, 2025)
Lesotho’s existing legislation and policy framework emphasises the commitment to providing access to inclusive education for all children, including children with disabilities. However, limited information exists regarding the education and placement of children with autism. This study explored the factors influencing parental decisions on educational placement for children with autism. A descriptive qualitative case study was employed, and eight parents of children with autism were interviewed face to face. The findings revealed significant variation in parental decisions and highlighted the complexity and frustrations inherent in decision-making. Key factors such as the child’s autistic traits, access to information, and school staff’s knowledge and experience with autism were identified as critical in shaping these decisions. The study highlights the need for collaborative support from all education stakeholders to ensure equal participation in the education system for children with autism. Such efforts are essential to reduce barriers, normalise challenges, and uphold the right to education for every child.